Adaptation to climate change through seasonal migration revealed by climatic versus demographic niche models. (13th April 2022) - Carbeck, Katherine; Wang, Tongli; Reid, Jane M.; Arcese, Peter
Abstract: Predicting the geographic range of species and their response to climatic variation and change are entwined goals in conservation and evolutionary ecology. Species distribution models (SDMs) are foundational in this effort and used to visualize the geographic range of species as the spatial representation of its realized niche. SDMs are also used to forecast range shifts under climate change, but often in the absence of empirical evidence that climate limits population growth. We explored the influence of climate on demography, seasonal migration, and the extent of the geographic range in song sparrows ( Melospiza melodia ), a species thought to display marked local adaptation to regional climate. To do so, we developed SDMs to predict the demographic and climate niches of migratory and resident song sparrows across our study area in western North America from California to Alaska, using 48 years of demographic data from a focal population in British Columbia and 1.2 million continental‐scale citizen science observations. Spatial agreement of our demographic and climate niche models in the region of our focal population was strong (76%), supporting the hypothesis that demographic performance and the occurrence of seasonal migration varied predictably with climatic conditions. In contrast, agreement at the northern (58%) and southern (40%) extents of our study area was lower, as expected if the factors limiting population growth vary regionally. Our results support the hypothesis that local climate drives spatial variation in the occurrence of seasonal migration in song sparrows by limiting the fitness of year‐round residents, and suggest that climate warming has favored range expansions and facilitated an upward shift in elevational range song sparrows that forgo seasonal migration. Our work highlights the potential role of seasonal migration in climate adaptation and limits on the reliability of climate niche models not validated with demographic data. Abstract : Climate niche models are used to forecast range shifts under climate change but often lack empirical evidence that climate limits population growth. We predict the demographic and climate niches of migratory and resident song sparrows in western North America, using 48 years of demographic data from a focal population in British Columbia and 1.2 million citizen science observations. Agreement between models in the region of our focal population was strong but deteriorated to the north and south. Our results highlight the potential role of seasonal migration in climate adaptation and limits of climate niche models not validated with demographic data.